2013
DOI: 10.1007/s00148-013-0470-z
|View full text |Cite
|
Sign up to set email alerts
|

Do more-schooled women have fewer children and delay childbearing? Evidence from a sample of US twins

Abstract: Using data on MZ (monozygotic, identical) female twins from the Minnesota Twin Registry, we estimate the causal effect of schooling on completed fertility, probability of being childless and age at first birth, using the within-MZ twins methodology. We find strong cross-sectional associations between schooling and the fertility outcomes and some evidence that more schooling causes women to have fewer children and delay childbearing, though not to the extent that interpreting cross-sectional associations as cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Neiss et al (2002) and Rodgers et al (2008) showed for the United States and Denmark respectively that the association between education and age at first birth is completely absorbed by latent family influences. Nisén and Myrskylä (2013) and Amin and Behrman (2014), however, found a significant link between both outcomes net of family influences. Our study suggests that a causal effect of education on age at first birth exists but that it is small and therefore might have remained undetected in former investigations.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Neiss et al (2002) and Rodgers et al (2008) showed for the United States and Denmark respectively that the association between education and age at first birth is completely absorbed by latent family influences. Nisén and Myrskylä (2013) and Amin and Behrman (2014), however, found a significant link between both outcomes net of family influences. Our study suggests that a causal effect of education on age at first birth exists but that it is small and therefore might have remained undetected in former investigations.…”
Section: Discussionmentioning
confidence: 94%
“…Although within-twin models have a long history in economics (Rosenzweig and Wolpin 1980) and psychology/behavioral genetics (D'Onofrio et al 2013;Neale and Cardon 1992), they have seldom been applied in demography (Amin and Behrman 2014). A comparison of the OLS and the within-twin approach indicates the extent to which family background leads to a spurious association between education and age at first birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 There is much research on the e¤ect of schooling on fertility, e.g., Amin and Behrman (2014), but this work does not ask about the fertility e¤ects of gender composition of study groups within education levels.…”
mentioning
confidence: 99%